Comparative analysis of N-terminal cysteine dioxygenation and prolyl-hydroxylation as oxygen-sensing pathways in mammalian cells - Tian, Ya-Min; Holdship, Philip; To, Trang Quynh; Ratcliffe, Peter J.; Keeley, Thomas P. (The Journal of biological chemistry, 2023)
In animals, adaptation to changes in cellular oxygen levels is coordinated largely by 2-oxoglutarate-dependent prolyl-hydroxylase domain (PHD) dioxygenase family members, which regulate the stability of their hypoxia-inducible factor (HIF) substrates to promote expression of genes that adapt cells to hypoxia. Recently, 2-aminoethanethiol dioxygenase (ADO) was identified as a novel O2-sensing enzyme in animals. Through N-terminal cysteine dioxygenation and the N-degron pathway, ADO regulates the stability of a set of non-transcription factor substrates; the regulators of G-protein signaling 4, 5. and 16 and interleukin-32. Here, we set out to compare and contrast the in cellulo characteristics of ADO and PHD enzymes in an attempt to better understand their co-evolution in animals. We find that ADO operates to regulate the stability of its substrates rapidly and with similar O2-sensitivity to the PHD/HIF pathway. ADO appeared less sensitive to iron chelating agents or transition metal exposure than the PHD enzymes, possibly due to tighter catalytic-site Fe2+ coordination. Unlike the PHD/HIF pathway, the ADO/N-degron pathway was not subject to feedback by hypoxic induction of ADO, and induction of ADO substrates was well sustained in response to prolonged hypoxia. The data also reveal strong interactions between proteolytic regulation of targets by ADO and transcriptional induction of those targets, that shape integrated cellular responses to hypoxia. Collectively, our comparative analysis provides further insight into ADO/N-degron-mediated oxygen sensing and its integration into established mechanisms of oxygen homeostasis.